Perancangan Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Menggunakan Metode Topsis Pada PT. Media Pariwara Indonesia - Zulfahmi Sengaji; Yudi Kurniawan (CV. Multi Kreasi Media, 2022)
Based on field studies conducted at PT. Media Pariwara Indonesia, the company always gives an assessment to each employee, this assessment is carried out to improve employee performance and performance and evaluate employee performance. In decision making there are several factors in determining employee performance appraisals so as to get the best employees. The best employee qualification standards have criteria that are expected to increase company productivity. The assessment includes attendance, cooperation, skills, loyalty, discipline and responsibility. In this study using the TOPSIS method because this method determines the weight value for each attribute followed by ranking a number of the best choices. By using this Topsis method, it can help and simplify the process of employee performance appraisal activities at PT. Media Advertising Indonesia is becoming more time and energy efficient